Effect of 6-weeks of endurance training on the activity of superoxide dismutase and glutathione peroxidase enzymes in the hippocampus of experimental diabetic male Wistar rats - Mohammad Rami (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd, 2018)
Introdution:Scientific evidence suggests the role of oxidative stress in diabetes and the development of its complications. Pre-preparation by aerobic exercise with increasing antioxidant power of neuronal cells can reduce oxidative stress and increase the resistance of the hippocampal region neurons.Therefore, the purpose of this study was to investigate the effect of 6weeks of endurance training on the activity of superoxide dismutase and glutathione peroxidase enzymes in the hippocampus of experimental diabetic male Wistar rats. Methods:In this experimental study, 24 male rats (245 ± 9.4 g) aged 10 weeks were divided into 4 groups of 6 rats each. The diabetic rats were diabetic by intraperitoneal injection of STZ. The exercise program included 6 weeks of moderate intensity endurance training. At the end of 6 weeks,the hippocampal tissue samples were extracted, 24 hours after the last training session. Descriptive one-way analysis of variance(ANOVA)was used in different group. If analysis were significant, differences between groups were estimated using Scheffe post-hoc test. Significance was defined as P≤0.0.Statistical analysis was performed using SPSS software version23. Results:After 6 weeks of endurance training, the level of superoxide dismutase in both groups, healthy training and diabetic training, was significantly increased, and in the diabetic control group, there was a significant decrease (P<0.001). Glutathione peroxidase levels in the two groups, training and healthy control group, were significantly different compare to the diabetic control group (P≥0.05).There was no significant difference between the three groups(P≥0.05). Conclusion:Based on the results, it can be concluded that endurance training may be effective in increasing the anti-oxidant defense of the hippocampal tissue of diabetic rats.